Determinan Individu dan Organisasi Dalam Implementasi Psikoedukasi Kesehatan Jiwa di Pelayanan Kesehatan Primer: Systematic Review - Taufiq Akbar; Bagoes Widjanarko; Ayun Sriatmi (Universitas Pahlawan Tuanku Tambusai, 2026)
Mental health disorders are a growing public health concern that require strengthened services at the primary health care level. The implementation of mental health psychoeducation is a key strategy to improve patient understanding, treatment adherence, and relapse prevention; however, it still faces various challenges. This study aimed to identify determinants influencing the implementation of mental health psychoeducation through a systematic review. The study followed PRISMA guidelines, with literature searches conducted in PubMed, Scopus, ScienceDirect, and Google Scholar from 2021 to 2026, yielding 1,222 articles. After the selection process, 18 articles met the inclusion criteria and were analyzed using thematic synthesis based on the CFIR framework. The findings indicate that individual factors, including knowledge, attitudes, motivation, and self-efficacy of health workers, as well as organizational factors such as leadership, policy support, and resource availability, are the main determinants. More than 50% of the studies emphasized the critical role of leadership and organizational support. Key barriers include high workload, limited training, stigma, and weak monitoring systems. In conclusion, implementation is influenced by the interaction between individual and organizational factors, highlighting the need for integrated approaches to improve service effectiveness. Keywords: Determinant factors, psychoeducation, officer factors, organizational factors